(untitled) (Journal of Parents and Teachers, 2024)
The article discusses the importance of abstraction and the creative search for solutions in learning. It is emphasized that students must understand mathematical principles in order to perform exercises and develop general concepts and procedures. In addition, the need to link different concepts and apply alternative methods to facilitate learning and creativity is mentioned.